Analysis of the Genetic Diversity and Origin of Some Chinese Domestic Duck Breeds - Yang ZHANG; Yang CHEN; Ting ZHEN; Zheng-yang HUANG; Chang-yi CHEN; Xin-yu LI; Xiu-jun DUAN; Biao DONG; Qi XU; Guo-hong CHEN (Journal of Integrative Agriculture, 2014)
Twelve fluorescence-labeled microsatellite markers were used to analyze the genetic diversity of 12 domestic duck breeds and 2 wild duck breeds to determine the relationship and origin of Chinese domestic duck breeds. Gene frequency, effective number of alleles (Ne), expected heterozygosity (He), polymorphism information contents (PIC), inbreeding coefficient in population (Fis), standard genetic distance (DS), and genetic distance (DA) were calculated by FSTAT and distance and phylogenetic analysis after the dates which were output from the Microsatellite-Toolkit software. Genetic distances between 12 domestic duck breeds and 2 wild duck breeds were analyzed by variance analysis. Unweighted pair group method with arithmetic mean (UPGMA) and phylogenetic trees used for cluster analysis were structured. The results indicated that 11 loci had medium- or high-level genetic diversity among the 12 loci, which could be efficiently used in the detection of the genetic parameters of each population. The values of He were 0.5414 to 0.7343, those of PIC proved similar, and those of Fis were 0.1101 to 0.3381 among all populations. All breeds were clustered into three groups by UPGMA phylogenetic trees. Banzui duck was clustered into a separate group. Differences of the DA were analysed by t-test. The results showed that difference in DA between the 12 domestic duck breeds and Lvtou duck and the Banzui duck were very significant (P<0.01), indicating that these 12 domestic duck breeds originated from Lvtou wild duck, but not Banzui duck.